Morphological diversity and genomic DNA fingerprinting of the African rice gall midge Orseolia oryzivora (Diptera: Cecidomyiidae) and of two other species of African Orseolia - Nwilene, F.E.; Harris, K.M.; Okhidievbie, O.; Onasanya, A.; Sere, Y.; Ingelbrecht, I.L. (Springer, 2006)
A morphological diversity study was conducted on African rice gall midge Orseolia oryzivora Harris & Gagné and two other African species, Orseolia bonzii Harris and Orseolia nwanzei Harris & Nwilene, sp. n. Morphological differences between adult and immature stages of the three species are slight and mainly evident in pupal characters. Due to limited differences in morphological characters, genomic DNA fingerprinting of these three insect species was carried out using random amplified polymorphic DNA (RAPD) and sequence-characterized amplified region (SCAR) methods. Out of 90 operon primers, 15 showed polymorphism among the three species tested, generating 86 bands, 60 (70%) of which were polymorphic. Primer OPV6 produced three RAPD markers that distinguished the three Orseolia species. These markers were cloned and sequenced. Their sequence was then used to design six SCAR primer pairs. Each SCAR primer pair amplified and distinguished the three Orseolia species at genomic DNA level. Both SCAR and RAPD genomic DNA fingerprinting revealed that O. oryzivora and O. bonzii are most closely related and O. nwanzei is distinct. Each of the six SCAR primer pairs produced a specific DNA fragment size specific for O. nwanzei, O. oryzivora and O. bonzii. The DNA fingerprints will be useful for entomological survey, identification of new species and differentiating aggressive from non-aggressive species, aimed at the effective development of rice cultivars with durable resistance to African rice gall midge.